Heavy-Ion Fusion Reaction Calculations: Establishing the Theoretical Frameworks for 111In Radionuclide over the Coupled Channel Model - Zehra Merve Cinan; Burcu Erol; Taylan Baskan; Ahmet Hakan Yilmaz (Energies, 2021)
In this work, the production of <semantics><mmultiscripts>I111</mmultiscripts>n</semantics> radionuclide has been investigated theoretically via heavy-ion fusion reactions of two stable nuclei: <semantics><mmultiscripts>C37</mmultiscripts>l+<mmultiscripts>G74</mmultiscripts>e</semantics>, <semantics><mmultiscripts>M26</mmultiscripts>g+<mmultiscripts>R85</mmultiscripts>b</semantics>, <semantics><mmultiscripts>S30</mmultiscripts>i+<mmultiscripts>B81</mmultiscripts>r</semantics>, and <semantics><mmultiscripts>C46</mmultiscripts>a+<mmultiscripts>C65</mmultiscripts>u</semantics> reactions. Fusion cross-sections, barrier distributions, and potential energies on mutual orientations in the reactions planes of all reactions have been researched in detail around the barrier region via a coupled channel (CC) model using different codes. First of all, the most suitable codes and calculation parameter sets were determined through the <semantics><mmultiscripts>C37</mmultiscripts>l+<mmultiscripts>G74</mmultiscripts>e</semantics> reaction, whose experimental data were available. The compatibility of the calculations via NRV knowledge base, CCFULL, CCDEF codes, and Wong’s formula with experimental data was analyzed. Barrier distributions and cross-sections for heavy-ion fusion reactions have been investigated with miscellaneous codes and vibrational-rotational nuclei combinations for interacting nuclei. Afterward, calculations were made with the determined parameter values for new reaction suggestions (<semantics><mmultiscripts>M26</mmultiscripts>g+<mmultiscripts>R85</mmultiscripts>b</semantics>, <semantics><mmultiscripts>S30</mmultiscripts>i+<mmultiscripts>B81</mmultiscripts>r</semantics>, and <semantics><mmultiscripts>C46</mmultiscripts>a+<mmultiscripts>C65</mmultiscripts>u</semantics> reactions) and the results were compared. This study aims to suggest the new reaction combinations for the production of 111In radionuclide, to explore the impacts of different calculation codes and nuclear parameter combinations on the heavy-ion fusion cross-sections and barrier distributions, to demonstrate that the results are reliable, and to emphasize the importance of developing these studies in the preparation of new experiments.